2016
DOI: 10.1039/c6nr07224k
|View full text |Cite
|
Sign up to set email alerts
|

A tunable nanopore sensor for the detection of metal ions using translocation velocity and biphasic pulses

Abstract: Citation: MAYNE, L.J., CHRISTIE, S.D.R. and PLATT, M., 2016. A tunable nanopore sensor for the detection of metal ions using translocation velocity and biphasic pulses. Nanoscale, 8, 19139-19147. Additional Information:• This paper was accepted for publication in the journal ) from solution. By tuning the pH and ionic strength of the solution, a biphasic pulse, a conductive followed by a resistive pulse is recorded. Biphasic pulses are becoming a powerful way to characterise materials, and provide an insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 59 publications
1
42
0
Order By: Relevance
“…In the absence of convection, the velocity of the carrier can be proportional to the surface charge or zeta potential (Blundell et al, ; Kozak et al, ). Here, the velocity is reported as 1/ T 0.5 values (Mayne et al, ), which we have previously shown capable of monitoring the length and packing density of DNA around SPBs (Blundell et al, ). As the density of the DNA and/ or its length increases, the velocity of the SPB through the pore also increases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of convection, the velocity of the carrier can be proportional to the surface charge or zeta potential (Blundell et al, ; Kozak et al, ). Here, the velocity is reported as 1/ T 0.5 values (Mayne et al, ), which we have previously shown capable of monitoring the length and packing density of DNA around SPBs (Blundell et al, ). As the density of the DNA and/ or its length increases, the velocity of the SPB through the pore also increases.…”
Section: Resultsmentioning
confidence: 99%
“…For example, they have been applied to the detection of metabolites (Alsager et al, ), proteins (Billinge, Broom, & Platt, ; Billinge & Platt, ; Siwy et al, ), DNA sequencing (Branton et al, ; Majd et al, ; Yeh, Zhang, Qian, & Hsu, ), epigenetics (Healey, Rowe, Siati, Sivakumaran, & Platt, ; Rand et al, ) and cellular vesicles (Kamińska et al, ; Nizamudeen, Markus, Lodge, Parmenter, & Platt, ). An increasingly common strategy in RPS utilizes nanomaterials as carriers of recognition elements to selectively bind to the target (Ali, Nasir, & Ensinger, ; Billinge et al, ; Billinge & Platt, , ; Lin, Ivanov, & Edel, ; Mayne, Christie, & Platt, ; Rotem, Jayasinghe, Salichou, & Bayley, ; Sze, Ivanov, Cass, & Edel, ). The carrier acts as a support for multiple ligands enhancing the signal and facilitating multiplexed assays (Blundell, Mayne, Billinge, & Platt, ; Platt, Willmott, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, measuring the translocation rates and velocities of the aptamer sequences through the pores, or finally the use of nanomaterials as carriers for multiple aptamers. 15,[21][22][23][24] The latter is appealing when the nanomaterials are Superparamagnetic Beads, SPB's, as the particles can perform both the purification and sensing roles. By adopting a tertiary structure in the presence of the target, the charge density around the SPB is altered.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] In cases where the charge double layers around the particles and pore walls interact, conductive pulses and ion current rectification can also be observed. 21,33,34 To help understand how the charge density effects the sensitivity of Aptamer RPS assays here we choose two known aptamers to heavy metal ions. The field of DNA-Metal ion sensors is growing and comprehensive review of the topic can be found elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, great effort has been made by the scientific community in order to develop devices and systems for metal ions detection. Electrochemical devices were initially proposed and in the last few years these kind of devices achieved high sensitivity and, in some special cases, also high selectivity by using nanomaterials as active electrodes [2][3][4]. However, these types of devices normally suffer the interferences from the electromagnetic noise sources.…”
Section: Introductionmentioning
confidence: 99%